(untitled) (Transport systems and technologies, 2018)
The paper describes a new scientific approach and a method of studying the problem associated with dual friction wedge-shaped wear of brake pads due to the presence of an edge upper shear which is formed during the train movement from imperfection of the brake system. The causes of uneven wear of brake pads are investigated, which leads to the slope of the pads and the pressure of the upper loop in the moving object of braking (wheel). The analysis of the results of field inspections during which the classification and types of demolition of the brake pads of the freight rolling stock were specified and updated, which allowed to approach the identification of the dynamic factors that correspond to the real scheme "Demolition of brake pads - Reason - Consequences" regarding the occurrence of transport events in the railway transport. To solve this problem, it is proposed to carry out the modernization of the brake lever transmission of freight carriages and to develop fundamental changes in its design, which substantially slows down the wedge-shaped demolition of the booms, will significantly increase the efficiency of their use and significantly increase the safety of the movement of rolling stock in the railroad. Also, some constructive solutions of known devices are considered in the article, which are aimed at slowing down the intensity of wear of brake pads of biaxial freight wagons, describing their shortcomings, and also measures for the modernization of the triangular system are proposed.